IGF2BP2 gene polymorphism in the pathogenesis of vitiligo - Kargun, Kursat; Demir, Betul; Cicek, Demet; Karstarli, Ozge Sevil (Funpec-Editora, 2017)
Vitiligo is a disorder of pigmentation presenting with loss of melanocytes in the epidermis and hair follicles. The gene for insulin-like growth factor binding protein 2 (IGF2BP2) is located on the third chromosome and it plays role in growth, development, cellular differentiation, and metabolism. In the present study, we aimed to investigate the rs1470579 and rs4402960 gene polymorphisms of IGF2BP2 in the patients with vitiligo, which were confirmed to have a relationship with insulin resistance. The study was conducted with a total of 100 patients with vitiligo between the ages of 18 to 60 years and 100 healthy controls. Gene polymorphism was investigated in deoxyribonucleic acid (DNA) samples isolated from blood cells using the real-time polymerase chain reaction (PCR) method. There was no statistically significant difference in the genotype and allele frequencies of the rs1470579 and rs4402960 polymorphisms on IGF2BP2 between the groups (p>0.05). Our study results show that the IGF2BP2 gene has no significant role in the pathogenesis of vitiligo.
Keywords: Vitiligo; IGF2BP2; Polymorphism